REALITAS SOSIAL DALAM SENI POSTER SEBUAH KAJIAN KARYA POSTER SHEPARD FAIRY - Dwi Haryanto (DeKaVe, 2013)
A poster, briefly dominated the visual element that is able to seize the attention of the audience ratherthan the verbal element. However, in fact that would be submitted by a poster is "i'!formation" or aparticular message. Obey Giant poster artwork which is the object of this study represent a designer,Shepard Frairy, in expressing ideas and imagination as part of the social environment in its own way.Though the visual imagination unusual phenomenon would lead to different design styles. Posters can bea medium of expression as a person over the sociological phenomenon.In describing a sociological study will be a lot of talk varied possibilities in understanding a work ofdesign, so that design work should be understood as a being who does not stand alone and require moreextensive exposure of the public support. Obey Giant poster-style works Shepar Fairy, in a sociologicalcontext does not appear out of nowhere and grows by itself into a large art construction. In the process,the work produced naturally through a social process.The process of creation of the work of Shepard Fairy gradually much influenced by several factorsthat are subjective (emotional factors, the nature, the power of images, and mental processes) as well asobjective factors that include factors of social institutions, society, geography, religion, and various otherfactors, so that the whole can be understood as a part of the components that build artistic construction ofthe designer.Keywords: Poster, Sociology, Social process